Taxonomic remarks on some Asian Lepidium s. l. (Brassicaceae) - German, Dmitry (Phytotaxa, 2014)
Taxonomy of some Central, Middle and South West Asian representatives of Lepidium s. l. is revised and updated. Poorly known taxon, L. rubtzovii, is shown to be unrelated to L. coronopifolium s. l., but close to L. lacerum. Three new combinations (L. lacerum subsp. rubtzovii, L. leventii, and L. macrocarpum) are proposed. The names L. deserti, L. persicum subsp. arianum and L. seravschanicum, and Stroganowia kazachstanica are newly recognized as synonyms of L. obtusum, L. ferganense, and L. cardiophyllum, respectively. For L. ferganense and L. macrocarpum, lectotypes are designated. Besides, L. lacerum subsp. rubtzovii is reported for the first time for China (instead of subsp. lacerum), L. leventii for Iran, L. macrocarpum for Tajikistan, and L. obtusum for Afghanistan. In contrast, occurrence of L. lacerum in Uzbekistan and Turkmenistan is considered doubtful.